Effect of oral health intervention program on the self oral care of children attending childcare facilities: a quasi-experimental study - Su-Jung Lee; Jong-Hwa Jang (Bioscience Journal, 2022)
This study aimed to conduct a quasi-experimental study for assessing the effects of an oral health intervention program (OHIP), on the self-management of oral health in children attending childcare centers. The participants recruited were 83 children from two childcare centers, who were allocated to the intervention and control groups. The intervention group received the OHIP. At baseline, a self-reported survey of parents was conducted. In addition, the oral status of the children at baseline and at 5 weeks was evaluated. Their brushing behavior was assessed once a week and every day during the OHIP intervention period and at home, respectively. After the follow-up at 12 weeks, dental plaque index (PI) was measured and two-way repeated measures analysis of variance was performed. The PI of the intervention group significantly decreased at week 5, compared to the baseline (1.90 ± 0.53, p < 0.001). Despite a substantial increase in week 12 (2.67 ± 0.08, p < 0.001), the PI was significantly lower than that of the control group (3.37 ± 0.60). The OHIP was effective in reducing the PI and modifying the brushing behavior among children. It is necessary to develop and expand a systematic oral health education program to promote self-management of oral health in children.